2022
DOI: 10.1002/ldr.4273
|View full text |Cite
|
Sign up to set email alerts
|

Spatial–temporal pattern of cultivated land productivity based on net primary productivity and analysis of influencing factors in the Songhua River basin

Abstract: Inefficient utilization puts the productivity of cultivated land in a low development state. The key challenge for the efficient utilization of cultivated land is to clarify how various factors affect the spatial differentiation pattern of cultivated land productivity (CLP), to improve food production. However, evaluating the impact of the intensity and direction of CLP on a large-scale is a difficulty and there is a gap in knowledge. In this study, we used net primary productivity (NPP) to calculate the produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 94 publications
1
7
0
Order By: Relevance
“…For another, the NDVI could somewhat reflect the amount of vegetation biomass and influence the distribution of NPP, as it is the best indicator of vegetation growth status and spatial distribution density. The results of this study were in agreement with the findings of Yang et al [39], who discovered that the greater values of NPP were distributed in regions with more vegetation cover. Moreover, a certain connection between the NDVI and NPP was identified, as the former was the main parameter for calculating the latter in the modified CASA model.…”
Section: Interpretation Of the Spatial Distribution Characteristics O...supporting
confidence: 93%
“…For another, the NDVI could somewhat reflect the amount of vegetation biomass and influence the distribution of NPP, as it is the best indicator of vegetation growth status and spatial distribution density. The results of this study were in agreement with the findings of Yang et al [39], who discovered that the greater values of NPP were distributed in regions with more vegetation cover. Moreover, a certain connection between the NDVI and NPP was identified, as the former was the main parameter for calculating the latter in the modified CASA model.…”
Section: Interpretation Of the Spatial Distribution Characteristics O...supporting
confidence: 93%
“…In the context of global change, spatial and temporal evolution and the driving mechanism of NPP are important topics in current NPP research. The study found that vegetation NPP is influenced by many factors, including temperature, precipitation, topography, soil, CO2, and human activities, and that the influencing factors vary greatly across regions [12][13][14]. Although scholars have conducted a lot of research on the driving force of NPP [15][16][17][18][19][20][21][22], they mostly choose climate factors, among which temperature and precipitation are the most commonly chosen.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the land parcel scale sample size is large and accurately reflects differences in ALH levels. features within localized areas (Yang et al, 2022).…”
Section: Alh At Different Spatial Scalesmentioning
confidence: 99%